Utilizing circulating free DNA in diagnosing early gastric cancer in a patient with situs inversus totalis: A case report and literature review. Issue 2 (3rd March 2021) - Jian, Wang; Huanqiu, Chen; Chao, Yue
Abstract: To offer a pilot view on the application of cfDNA in diagnosing early gastric cancer in patient with situs inversus totalis (SIT), accompanied by a literature review. Within this study, we assessed the feasibility of diagnosing early gastric cancer in a SIT patient by detecting cfDNA concentration and mutations. Meanwhile, a search through PubMed using key words of "situs inversus totalis and gastric cancer" covering English studies from 2008 to 2019 was carried out to provide an associated literature review. Of all the 24 publications we reviewed, 25 patients were diagnosed with SIT and GC. The majority of them (23/25) were from the eastern Asia area. More than 40% (11/25) of the patients were diagnosed at advanced tumor stages. In the case of an early staged GC in our center, when both radiographic and endoscopic exams failed to establish an accurate diagnose, we found that not only the concentration of cfDNA was above normal, the frequent genetic mutations for GC were also detected within preoperative cfDNA. The concomitance of SIT and GC is still a rare incident, only limited cases have been reported and were often diagnosed in late cancer stages. By measuring the concentration and mutations of cfDNA, early GC may be detected in SIT patients.